Neoliberalism in education: Five images of critical analyses - Branislav Pupala; Ondrej Kaščák (Pedagogická Orientace, 2011)
The survey study brings information about the way that educational researchcopes with neoliberalism as a generalized form of social government in the currentwestern culture. It shows that neoliberalism is considered as a universal scope of otherchanges in the basic segments of education and those theoretical and critical analyses ofthis phenomenon represent an important part of production in the area of educationalresearch. It emphasizes the contribution of formation and development of the socalledgovernmental studies for comprehension of mechanisms and consequences ofneoliberal government of the society and shows how way the methodology of thesestudies helps to identify neoliberal strategies used in the regulation of social subjectsby education. There are five selected segments of critical analyses elaborated (fromthe concept of a lifelong learning, through preschool and university education to theeducation of teachers and PISA project) that obviously show ideological and theoreticalcohesiveness of the education analysis through the scope of neoliberal governmentality.